Urine S100 BB and A1B dimers are valuable predictors of adverse outcome in full‐term asphyxiated infants. (8th August 2013) - Risso, Francesco M; Serpero, Laura D; Zimmermann, Luc JI; Gavilanes, Antonio WD; Frulio, Rosanna; Michetti, Fabrizio; Florio, Pasquale; Bashir, Moataza; Iskander, Iman; Mufeed, Hala; Aboulgar, Hanna; Gazzolo, Diego
Abstract: Aim: To investigate whether S100A1B and BB dimers are predictors of early perinatal death in newborns with perinatal asphyxia (PA). Methods: The study compared 38 full‐term newborns with PA [neonatal death n = 11; hypoxic ischaemic encephalopathy (HIE): n = 27] with a control group of 38 healthy infants. Clinical and laboratory parameters were recorded at eight time points and urine collected for S100B assessment. Multivariate analysis was performed in order to analyse the influence of various clinical parameters on the occurrence of neonatal death. Results: A1B and BB in PA nonsurvivor infants were significantly higher (p < 0.001) than in controls at all monitoring time points. BB at first void (cut‐off>42 ng/L) was the best predictor of early neonatal death (p < 0.05) of all the clinical and laboratory parameters studied. Conclusion: These results suggest that S100s are valuable predictors of adverse outcome in PA infants. It is also suggested that these biomarkers be used in daily clinical practice, due to their low cost and stress, reproducibility and the possibility of longitudinal monitoring.